1985
DOI: 10.1111/j.1476-5381.1985.tb08838.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tolbutamide metabolism by substituted imidazole drugs in vivo: evidence for a structure‐activity relationship

Abstract: 1 Tolbutamide has been used as a model drug for an examination of the effects of eleven substituted imidazole compounds on hepatic metabolism in vivo. 2 The 1-substituted compounds 1-methylimidazole, miconazole, clotrimazole and ketoconazole produced marked alterations in tolbutamide kinetics (increased half-life, decreased clearance). However, if there was substitution in the 2-position, irrespective of a substituent on N-1, then the compound did not appear to inhibit metabolism (e.g. 2-methylimidazole, 1,2-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 16 publications
(15 reference statements)
1
7
0
Order By: Relevance
“…Cimetidine was a comparatively weak inhibitor and this is consistent with the in vivo data which indicates an increase in tolbutamide half-life with a cimetidine dosage regimen of 1600 mg day-' but not 800 mg day-' (Dey et al, 1983;Cate et al, 1986;Stockley et al, 1986;40 200 CL i.O4 Back et al, 1988). The antimycotic drugs ketoconazole and clotrimazole were potent noncompetitive inhibitors of tolbutamide hydroxylase and this is consistent with previous findings of inhibition of the oxidation of many other substrates, both in vitro and in vivo (Sheets & Mason, 1984;Back & Tjia, 1985;Brown et al, 1985;Meredith et al, 1985;Cockburn, 1986;Sheets et al, 1986;Lavrijsen et al, 1987). The mechanism of interaction, studied in considerable detail by some of the above workers, is considered to be binding of the imidazole-3-N to the ferric form of the haemoprotein as a sixth ligand.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cimetidine was a comparatively weak inhibitor and this is consistent with the in vivo data which indicates an increase in tolbutamide half-life with a cimetidine dosage regimen of 1600 mg day-' but not 800 mg day-' (Dey et al, 1983;Cate et al, 1986;Stockley et al, 1986;40 200 CL i.O4 Back et al, 1988). The antimycotic drugs ketoconazole and clotrimazole were potent noncompetitive inhibitors of tolbutamide hydroxylase and this is consistent with previous findings of inhibition of the oxidation of many other substrates, both in vitro and in vivo (Sheets & Mason, 1984;Back & Tjia, 1985;Brown et al, 1985;Meredith et al, 1985;Cockburn, 1986;Sheets et al, 1986;Lavrijsen et al, 1987). The mechanism of interaction, studied in considerable detail by some of the above workers, is considered to be binding of the imidazole-3-N to the ferric form of the haemoprotein as a sixth ligand.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we have examined a number of imidazole and aminoquinoline derivatives. Many of these compounds have previously been shown to be inhibitors of oxidative enzymes (Back etal., 1983a,b;Murray, 1984;Thabrew & Ioannides, 1984;Sheets & Mason, 1984;Back & Tjia, 1985;Brown et al, 1985;Meredith et al, 1985;Mihaly et al, 1985;Riviere & Back, 1985, 1986Cockburn, 1986;Sheets et al, 1986;Lavrijsen et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the majority of The possibility remains that 4-MEI may act in the mouse lung by binding to or inhibiting 532 a specific CYP enzyme differently than in rats. Back and Tjia (1985) reported that 4-533 MEI inhibited CYP activity in rat liver. Similarly, Hargreaves et al (1994) reported that 534 4-MEI was a strong inhibitor of rat liver CYP2E1.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…Many of the azole antimycotics, including ketoconazole, in addition to inhibiting fungal P-450, also inhibit hepatic oxidative enzymes. This is because these compounds have readily accessible non-bonded electrons on a nitrogen atom, the imidazole 3-N, enabling them to bind (Type II interaction) to the ferric form of the haemoprotein as a sixth ligand (Sheets & Mason, 1984;Back & Tjia, 1985;Meredith et al, 1985;Brown et al, 1985;Sheets et al, 1986;Lavrijson et al, 1987;. In contrast, terbinafine is a Type I substrate for a small portion of cytochrome(s) P-450 of hepatic microsomes (Schuster, 1987).…”
Section: Introductionmentioning
confidence: 99%